MONITORING AND MODELLING OF AIR POLLUTION PRODUCED BY AIRCRAFT ENGINE EMISSION INSIDE THE ATHENS INTERNATIONAL AIRPORT - Zaporozhets, Oleksander I.; Synylo, Kateryna V. (Proceedings of National Aviation University (archive), 2009)
Experimental measuring of air pollution inside the airport, produced by aircraft engine emission during accelaration and take-off on the runway. Measurement data were used for verification of modelling results according to complex model «PolEmiCa». It consists of the following basic components: engine emission inventory calculation; transport of the contaminants by engine jets, dispersion of the contaminants in atmosphere due to wind and atmospheric turbulence.